The Impact of the COVID‐19 Lockdown on Obstetrics Practice at a Rural Based Tertiary Care Centre: An Analytical Crossectional Study - Singh, Dr. Amrita; Kawthalkar, Dr. Anjali; Nyase, Jaydeep; Sontakke, Dr. Priya (International Journal of Innovative Research in Medical Science, 2021)
Objective: To evaluate the impact of the COVID‐19 lockdown on obstetrics practise in a tertiary care centre. Methods: Analytical Crossectional observational study was conducted in the obsgyn department from Jan 2020 to June 2020.There were two groups pre lockdown (Group B) and post lockdown (Group A) of 180 women in each group. Results were analysed using Epi info software version 7. Results: There was significant (p < 0.001) rise in LSCS rates (80%) in post lockdown period as compared to prelockdown (50%). Emergency LSCS (87.5%) was seen more during pandemics as compared to elective LSCS (12.5%). Elective LSCS was seen more prior to lockdown. The gestational age during admission in lockdown was more in <37 weeks gestation group with complications or >40 weeks. Significant rise (p< 0.001) in IUD (13.3%), NICU admissions (23.3%) were noted during lockdown as compared to prelockdown (6.6%), (10%). Hospital stay was reduced from 4 days to 3 days during the lockdown. Conclusion: Lockdown affects obstetrics outcome adversely. There is an urgent need to sensitize antenatal women as well as health care workers to continue the routine obstetrics care, especially in the second half of pregnancy with covid appropriate behaviour.